PERLINDUNGAN HUKUM KORBAN KEKERASAN SEKSUAL TPPO - A, Andi Fadli.; Natsir, Muhammad; Syam, Elvi Susanti; Tijjang, Bakhtiar; Purwanda, Sunardi (Ipso Jure, 2025)
This study aims to analyze the legal protection provided to victims of sexual violence in human trafficking crimes (Tindak Pidana Perdagangan Orang or TPPO) within the Indonesian legal framework. Sexual violence as a form of exploitation in human trafficking represents a severe violation of human rights that undermines the dignity and safety of its victims. Using a normative juridical approach, this research focuses on the examination of legal instruments, including Law No. 21 of 2007 concerning the Eradication of the Crime of Human Trafficking, Law No. 12 of 2022 on the Crime of Sexual Violence, and related provisions in the Criminal Code (KUHP). The study highlights that legal protection for victims of sexual exploitation under TPPO encompasses preventive, repressive, and rehabilitative measures. However, implementation remains constrained by weak law enforcement, lack of coordination among institutions, and inadequate victim recovery mechanisms. Findings indicate that strengthening victim-centered legal frameworks, ensuring comprehensive rehabilitation, and improving access to justice are crucial to achieving substantive protection for victims. This research contributes to a better understanding of how Indonesia’s criminal law should evolve to provide holistic protection and justice for victims of sexual violence in human trafficking cases, aligning with international human rights standards.